Selected Lectures of the 14th International Workshop on Neonatology; Cagliari (Italy); October 24th-27th, 2018 - - (Hygeia Press di Corridori Marinella, 2018)
Selected Lectures of the 14th International Workshop on Neonatology; Cagliari (Italy); October 24th-27th, 2018 • THE REVOLUTION OF MICROBIOMICS • NUTRITION, BACTERIA AND PROBIOTICS IN PERINATAL AND PEDIATRIC HEALTH LECT 1. PERINATAL PROGRAMMING: FROM THE WOMB TO THE ADULT. THE FIGO LIFE CYCLE APPROACH • M. Hod LECT 2. SINS IN PREGNANCY, SINS, AND PREGNANCY • G.C. Di Renzo LECT 3. THE HUMAN MILK AS A MODEL OF PREVENTION • G. Corsello, M. Carta LECT 4. LESS INVASIVE SURFACTANT ADMINISTRATION (LISA): WHERE ARE WE NOW? • E. Herting LECT 5. DRUGS AND NEUROPROTECTION • S. Perrone, E. Laschi, G. Nanni, G. Buonocore LECT 6. CRANIOFACIAL DEFORMATIONS BETWEEN ART AND SCIENCE • F. Velardi LECT 7. NON-NUTRITIVE SUCTION AND BREATHING IN PRETERM INFANTS • S. Ossola, V. Trivellin, M. Ragazzo, F. Riccaboni, L. Montericcio, L. Nosetti, S. Salvatore, L. Levrini, M. Agosti LECT 8. PARENTERAL NUTRITION IN VERY LOW BIRTH WEIGHT INFANTS: TO STANDARDIZE OR NOT TO STANDARDIZE? • S. Iacobelli, F. Bonsante LECT 9. PULMONARY HYPERTENSION: ANY NEWS? • M. Sánchez Luna LECT 10. PERSISTENT DUCTUS ARTERIOSUS: TO CLOSE OR NOT TO CLOSE? • C. Dani LECT 11. MONITORING CARDIOVASCULAR PARAMETERS IN NICU • D. Doni, P.E. Tagliabue LECT 12. DO NOT ATTEMPT RESUSCITATION (DNAR) ORDERS, WITHDRAWING/WITHHOLDING CARE IN THE NICU • P. Biban, S. Lauriola, M. Ventola, C. Forcellini, B. Ficial, F. Bissolo, E. Bonafiglia, L. Chini, L. Pecoraro, I. Sibona, R. Frassoldati, R. Beghini LECT 13. VITAMINS IN THE NEWBORN • C. Romagnoli LECT 14. ANEMIA OF PREMATURITY: WHAT METABOLOMICS CAN ADD • V. Fanos, R. Pintus, F.S. Corbu, G. Ledda, E. Coni, A. Dessì, M. Puddu, F. Cesare Marincola LECT 15. IRON STATUS AND LATE PRETERM INFANTS • R. Luciano LECT 16. NEONATAL TRANSFUSION PRACTICE • C. Franco, F. Petrillo, K. Del Vecchio, G. D'Amato, A. Del Vecchio LECT 17. INDIVIDUALIZED DEVELOPMENTAL CARE STABILIZING SLEEP, MOVEMENT, POSTURE AND CARDIORESPIRATORY CONTROL PROTECTS THE BRAIN IN THE NICU • F. Ferrari, N. Bertoncelli, E. Garetti, E. Della Casa, M.F. Roversi, L. Ori, L. Lucaccioni LECT 18. POINT OF CARE TESTING (POCT) INNOVATION, CONNECTED HEALTH AND BEYOND - HOW DIGITAL TECHNOLOGY IS TRANSFORMING LABMED, HEALTH, AND SOCIAL CARE? • S. Bernardini LECT 19. MICROBIOME IN FORENSIC SCIENCE • B. Benedetti, P. Roberti, E. d'Aloja LECT 20. MICROBIOME AND PROBIOTICS IN THE PERINATAL ARENA • N. Giovannini LECT 21. MICROBIOTA, PROBIOTICS AND PREBIOTICS • F. Indrio, V. Dargenio LECT 22. URINARY MICROBIOTA: IS THERE ANY DIFFERENCE IN CHILDREN WITH URINARY TRACT DISEASE? • G. Masnata, M. Limone, V. Manca LECT 23. METABOLOME AND MICROBIOME IN AUTISM: THE LAST DATA • M. Mussap, V. Fanos LECT 24. MODE OF CHILDBIRTH AND EFFECT ON NEONATAL AND MATERNAL HEALTH AND DISEASES • A. Ragusa, S. Rugolotto, A. Svelato, C. Incarnato LECT 25. PRETERM LABOR FROM THE SOCIETY FOR MATERNAL-FETAL MEDICINE (SMFM) POINT OF VIEW: AN UPDATE • T. Frusca LECT 26. BIG DATA, ULTRASOUND, AND NEONATAL RESPIRATORY DISTRESS: ANYTHING IN COMMON? • F. Raimondi LECT 27. GESTATIONAL DIABETES • F. Mecacci LECT 28. GESTATIONAL DIABETES FROM A PEDIATRIC VIEWPOINT • R. Antonucci, C. Locci LECT 29. EXCESSIVE GESTATIONAL WEIGHT GAIN: INTERVENTIONS AIMED TO REDUCE THE EFFECTS ON MATERNAL AND OFFSPRING HEALTH • L. Di Cerbo, D. Menichini, F. Facchinetti LECT 30. "TOO MUCH" AND "NOT ENOUGH" WEIGHT IN PREGNANCY • A. Dessì, M. Puddu, V. Fanos LECT 31. UNRAVELING THE COMPLEX GENETICS OF CHILDHOOD AND ADOLESCENT PSYCHOPATHOLOGY, INCLUDING AGGRESSION, THROUGH INTERNATIONAL COLLABORATIONS: AN UPDATE ON THE CAPICE AND ACTION PROJECTS • M. Manchia, V. Fanos LECT 32. THE ROLE OF BIG DATA IN NEUROPSYCHIATRIC DISORDERS: A FOCUS ON METABOLOMICS • H.S.R. Rajula, M. Manchia, V. Fanos LECT 33. SHARING RESEARCH: COMMUNICATION CAN HELP • M. Mauri, V. Fanos LECT 34. ENDOCRINE DISRUPTORS AND NEURODEVELOPMENT • M.E. Street, F. Cirillo, C. Catellani, P. Palanza, G.C. Panzica, E. Grossi, P. Lazzeroni, C. Sartori LECT 35. MATERNAL-INFANT HEALTH CARE: QUESTIONS AND ISSUES ON AN INTEGRATED PRACTICE • G. Perricone LECT 36. URINARY GC-MS METABOLOMICS COMPARISON BETWEEN TWO COHORTS OF TODDLER AND ADOLESCENT SUBJECTS AFFECTED BY AUTISM SPECTRUM DISORDER • A. Noto, C. Fattuoni, M. Mussap, L. Barberini, M. Siracusano, L. Mazzone, R. Francavilla, P. Curatolo, V. Fanos LECT 37. LUNG MICROBIOTA • U. Pelosi, R. Pintus LECT 38. THE EXCEPTION CONFIRMING THE RULE • G. Ottonello, F. Bardanzellu, M.E. Trudu, G.Z. Trapletti, G. Masnata LECT 39. DIARRHEA, GASTROENTERITIS, AND INFLAMMATORY BOWEL DISEASE: THE RATIONALE OF PROBIOTICS • M. Corpino LECT 40. IRON AND GASTROINTESTINAL DISEASES • M.G. Clemente LECT 41. HOW TO FEED THE GUT MICROBIOTA • G. Biasucci LECT 42. HUMAN MILK, BACTERIA, AND ALLERGIC OUTCOMES • D. Peroni, M.E. Di Cicco, P. Comberiati LECT 43. INFANT EXPOSURE - HISTORICAL AND ANTHROPOLOGICAL NOTES • L. Cataldi, M.G. Gregorio LECT 44. THE BABY HATCH OF THE THIRD MILLENNIUM • P. Paolillo, F. Di Palma, S. Picone LECT 45. NON-INVASIVE TEST FOR PRENATAL DIAGNOSIS OF CONGENITAL DISEASES AND PREGNANCY TUMORS • G. Floris LECT 46. LUNG PATHOLOGY IN THE NEWBORN: A NEW CT SCAN-BASED SAMPLING METHOD ALLOWS A BETTER ANALYSIS OF THE IMMATURE LUNG IN RESPIRATORY DISTRESS SYNDROME • G. Faa, C. Gerosa, R. Garau, V. Marinelli, C. Moretti, F. Cau, C. Loddo, V. Fanos LECT 47. STAINED AMNIOTIC FLUID: WHAT'S NEW? • A.M. Fulghesu, E. Canu, L. Barberini, C. Fattuoni, V. Fanos LECT 48. MYSTERIES OF THE PERINATAL HEARTH • A. Faa, E. Podda, G. Faa, V. Fanos LECT 49. THE KIDNEY: A FASCINATING AND MYSTERIOUS ORGAN • C. Gerosa, D. Fanni, V. Fanos, G. Faa LECT 50. SECRETS OF THE BRAIN • M. Vendemmia LECT 51. FOCUS ON... MITOCHONDRIA • F. Bardanzellu, M.C. Pintus, V. Fanos, M.A. Marcialis LECT 52. THE EXTRAORDINARY REGENERATIVE POWER OF HUMAN ENDOMETRIUM • F. Bardanzellu, G. Faa, D. Fanni, V. Fanos, M.A. Marcialis LECT 53. PLACENTA AND METABOLOMICS • L. Barberini LECT 54. PERINATAL ENDOMETRIOSIS • S. Angioni, F. Dessolis LECT 55. PEDIATRIC FATTY LIVER DISEASE • D. Fanni, C. Gerosa, G. Faa LECT 56. THE QUESTIONS OF THE MOTHERS • A. Dessì LECT 57. DORIS AND THE OTHER CHILDREN WHO TOOK CARE OF ME... • P. Zanolla LECT 58. METABOLOME AND MICROBIOME IN PERINATAL MEDICINE: AN UPDATE • V. Fanos, M. Mussap LECT 59. NEONATOLOGICAL ORTHOPEDIC CASE REPORTS • V. Setzu, A. Dolci